2002
DOI: 10.1542/peds.110.3.577
|View full text |Cite
|
Sign up to set email alerts
|

National Practices Regarding Payment to Research Subjects for Participating in Pediatric Research

Abstract: IRBs must balance the need to recruit pediatric research subjects against the risk of undue influence during the recruitment process. Federal guidelines and expert pediatric opinion differ in recommendations regarding payment; responding IRBs appeared to follow federal guidelines more closely than guidelines proposed by the American Academy of Pediatrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 5 publications
2
40
0
Order By: Relevance
“…Some authors have raised concerns that payments to underserved populations represents coercion, while others have suggested that payments may bias study results obtained or population recruited. [73][74][75][76][77][78][79] Accordingly, payments could potentially have a negative impact on trust, especially in vulnerable populations that might already be distrustful of research.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have raised concerns that payments to underserved populations represents coercion, while others have suggested that payments may bias study results obtained or population recruited. [73][74][75][76][77][78][79] Accordingly, payments could potentially have a negative impact on trust, especially in vulnerable populations that might already be distrustful of research.…”
Section: Discussionmentioning
confidence: 99%
“…In research involving children, the offer of payment is doubly problematic because often the person receiving payment is the parent or guardian when it is the child who is being exposed to the risk and burden of the study. 28 Some have argued that parents should not receive monetary payments for their child' s research participation, 29 whereas others believe that payment can reimburse research-related expenses and failure to compensate for these expenses may lead to the exclusion of poorer families. Payment can also compensate for time and inconvenience, act as a token of appreciation after children have participated, or act as an incentive to encourage participation.…”
Section: Payment For Research: Justified or Unethical?mentioning
confidence: 99%
“…Consequently, some find carefully calculated payment to compensate parents for time and inconvenience acceptable and unlikely to contribute to significant distortions in parental judgment (53), while others believe that compensation to parents should be limited to reimbursement for expenses (51). The American Academy of Pediatrics recommends the giving of gifts instead of money to children in a post-trial appreciation model (54), although many institutions do not appear to follow these recommendations (55). Giving money or non-cash gifts to children directly instead of to their parents is also difficult because children appreciate money and gifts differently depending on their age.…”
Section: Payment Of Children In Researchmentioning
confidence: 99%